How effective is phonological awareness training for preschoolers with speech and language difficulties? Exploring the perspectives of teachers working in preschool settings in Dubai. - O’NEILL, LEAH MARIE (2022)
Abstract Background: It is well documented throughout the literature that phonological awareness (PA) development in early education is a strong predictor of later reading success. Children with speech and/or language (S&L) impairments are at an increased risk of PA deficits and may face ongoing challenges and persistent difficulties, which impact literacy and language outcomes and academic success beyond the preschool classroom. Aims: This qualitative study aims to explore how preschool teachers perceive the effectiveness of PA instruction for children with S&L difficulties. Methods and Procedures: Forty preschool teachers working in private preschool settings in Dubai, UAE, were recruited. Following an initial survey to ascertain teacher knowledge about PA instruction in early education, teachers were invited to participate in a 4-week online training program aimed at developing PA skills in preschool children with S&L difficulties. 30% of the sample completed semi-structured interviews or a questionnaire following the intervention phase. Thematic analysis was applied and involved a process of manual coding to construct and interpret themes based on patterns that emerged from the data reflecting preschool teachers' perspectives. Findings: The themes identified in this study are consistent with findings found in the literature. Teachers expressed that they lacked knowledge and skills regarding PA assessment and intervention methods. Similarly, teachers expressed that they lacked appropriate training to effectively support children with S&L difficulties in the preschool classroom. Whilst teachers acknowledged the need for early intervention and recognised the importance of PA in early literacy development for children with S&L deficits, they expressed limited opportunities to engage in collaborative practice alongside speech and language therapists (SLTs) who are experts in the field. Thus, professional development opportunities are warranted within preschool settings in Dubai as findings highlight the need to improve teaching practices and provision for children with lower levels of language and literacy abilities. Furthermore, preschools must ensure that inclusion policies are reflected in practice so that children with additional educational needs have equal and equitable opportunities to access learning alongside typically developing peers. Therefore, policymakers and stakeholders must closely monitor and evaluate the quality of provision. The findings also reinforce the need for initial teacher training courses to be reviewed so that early educators enter the classrooms better equipped with knowledge, tools, confidence and strategies to effectively meet the needs of all preschool children.